Research on gas concentration identification based on sparrow search algorithm optimization SVR - Zhang, Yuanman; Zou, Yanan; Wu, Qingyun (International journal on smart sensing and intelligent systems, 2025)
To address the challenge of quantitatively identifying mixed gases, we developed a gas concentration identification algorithm based on the sparrow search algorithm (SSA) and optimized support vector regression (SVR). The Tent chaotic mapping operator is employed to initialize the population, enhancing population diversity, and improving the algorithm’s global search capability. By optimizing SVR parameters with SSA, we propose an enhanced TSSA-SVR model. Evaluated on mixed gas datasets, TSSA-SVR achieves a prediction accuracy of 94.47%, outperforming comparative algorithms such as Genetic Algorithm (GA)-SVR and PSO-SVR, while demonstrating improved convergence compared to the baseline SSA-SVR. The experimental results demonstrate significant performance enhancements, offering an effective solution for precise gas concentration identification in complex environments.